Isolation and identification of resistance Staphylococcus aureus to vancomycin & Methicillin from outpatients clinic in AL-Shefa General Hospital in Basrah district - .AL-Mosawi, R.M.M (University of Thi-Qar Journal of Science, 2010)
Research doing on isolation and identification of S.aureus resistance to vancomycin and Methicillin on 547 samples outpatient ( adults and non –adults) clinic of Al Shefa General Hospital in Basrah district during the period from October, 2007 to March, 2008, their age was ranged from 5-65 years.One urine sample was collected from each patient under investigation and cultured by the streaking method onto Enrichment media and Selective (differential) media because of the common urinary pathogens and other pathogens grow well on these cultures media.For isolation species depending to genus staphylococcus especially S.aureus (COPS) and (CONS); the samples urine streaking on Mannitol-Salt agar (selective media), the biochemical reactions (identification tests) were doing for staphylococcus Spp. especially COPS, CONS and other bacterial species in dependence on Bergey’s Manual of Determinative Bacteriology (Holt et.al., 1994).Furthermore, two antimicrobial agents were used in this research : Vancomycin in (30 mg) and methicillin ( 5 mg) for antimicrobial susceptibility test to S.aureus bacterial isolates (COPS); (CONS).Results showed that the highest isolation rate of infection with S.aureus in cases: VRSA,VISA and VSSA were correlated with age group above 50 years in proportion: 7.93% , 4.76% and 12.69% respectively. Also, the Methicillin Resistance Staphylococcus aureus (MRSA) was recovered 6.42% and 9.52% in age groups above 50 years. The MR Staphylococci (CONS) was isolated in this study in proportion 4.76%.